2018
DOI: 10.1021/acs.langmuir.7b03626
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and Fibrillization of Islet Amyloid Polypeptide at Self-Assembled Monolayers Studied by QCM-D, AFM, and PM-IRRAS

Abstract: Aggregation and fibrillization of human islet amyloid polypeptide (hIAPP) plays an important role in the development of type 2 diabetes mellitus. Understanding the interaction of hIAPP with interfaces such as cell membranes at a molecular level therefore represents an important step toward new therapies. Here, we investigate the fibrillization of hIAPP at different self-assembled alkanethiol monolayers (SAMs) by quartz crystal microbalance with dissipation monitoring (QCM-D), atomic force microscopy (AFM), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(74 citation statements)
references
References 59 publications
1
61
0
Order By: Relevance
“…Due to the application of selected transduction techniques in chemo- and bio-sensors [ 18 , 19 , 20 , 21 , 22 , 23 ], it is possible to evaluate the deposition degree of particular materials [ 24 ], for instance in the form of self-assembled monolayers (SAM) [ 12 , 25 ], and to analyze gas phase composition [ 14 , 26 , 27 ]. Nowadays, the priority in design and development of QCM analytical platforms is given to naturally occurring compounds, since they are excellent receptors with superior selectivity for the target analytes [ 28 ].…”
Section: Qcm Technology Basicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Due to the application of selected transduction techniques in chemo- and bio-sensors [ 18 , 19 , 20 , 21 , 22 , 23 ], it is possible to evaluate the deposition degree of particular materials [ 24 ], for instance in the form of self-assembled monolayers (SAM) [ 12 , 25 ], and to analyze gas phase composition [ 14 , 26 , 27 ]. Nowadays, the priority in design and development of QCM analytical platforms is given to naturally occurring compounds, since they are excellent receptors with superior selectivity for the target analytes [ 28 ].…”
Section: Qcm Technology Basicsmentioning
confidence: 99%
“…This technique is widely utilized for investigation of the aggregation process as well as identification and characterization of inhibitors and modulators of that process. Evaluation of the rate of fibril growth on different surfaces is currently widely examined [ 96 , 97 ], as well as the possibility of QCM-D application to study amyloid aggregation upon contact with various model surfaces, for example double lipid layers, self-assembled monolayers (SAMs), and metal oxides [ 25 , 83 , 98 , 99 , 100 ]. The benefits stemming from monitoring of dispersion changes include the option of discrimination between the types of amyloid adsorption [ 85 ] and characteristic fibril growth and conformations [ 25 ].…”
Section: Adsorption Of Peptide and Protein Molecules On The Qcm Sumentioning
confidence: 99%
See 2 more Smart Citations
“…The S 2p level of -OH, -COOH, -CH 3 , and -NH 2 SAMterminated surfaces were studied, and it has been found that the partial oxidation of -SH to sulfonate happened only in NH 2 terminated SAM, which could be attributed to the HCl used to stabilize amino compound. 52 Table 2 demonstrates the properties of the four types of SAMs. The sessile drop method was used to measure the deionized water contact angle on SAM coated sensors.…”
Section: Characterization Of Self-assembled Monolayers (Sam)mentioning
confidence: 99%